Inhibition of off-target cleavage by RNase H using an artificial cationic oligosaccharide. Issue 31 (29th July 2021) - Hara, Rintaro Iwata; Wada, Takeshi
Abstract : We describe a novel strategy to inhibit off-target cleavage by RNase H using an artificial cationic oligosaccharide, which bind to DNA/RNA hybrid duplexes. Abstract : Sequence-dependent off-target effects are a serious problem of antisense oligonucleotide-based drugs. Some of these side effects are induced by ribonuclease H (RNase H)-mediated cleavage of non-target RNAs with base sequences similar to that of the target RNA. We found that an artificial cationic oligosaccharide, ODAGal4, improved single-base discrimination for RNase H cleavage.